A Case Study of Getting Performance Characteristics of a Salient Pole Synchronous Hydrogenerators - Topaloğlu, İ. and Ocak, C. and Tarımer, İ. (Elektronika ir Elektrotechnika, 2010)
Today, continuously increasing electrical energy demand makes every one to investigate how to benefit maximum efficiency from hydro–electric power plants’ generators. In this study, 560 kW, 400 V, 1000 rpm, 6 pole salient pole synchronous machine’s heat, excited voltage, efficiency and losses have been researched to see the influence on hydrogenerators and to design a suitable model for natural running environment. In addition to these, the field current versus stator current under various load conditions has been determined and the reactive capability of a hydrogenerator has been calculated. It has been seen that the performance characteristics of the designed hydrogenerator was directly related with the running environment and the load conditions. Ill. 5, bibl. 22, tabl. 2 (in English; abstracts in English, Russian and Lithuanian).